Linear poly(lactic acid) ionomers with pendant ionic groups - Joseph, Seena; Menon, Abhijith Hari; Lele, Ashish K.; Chikkali, Samir H. (New Journal of Chemistry, 2024)
Although PLA is widely used, melt processing of this polymer is still a challenging task. In our efforts to improve the melt strength and processability of PLA, we report the synthesis of high molecular weight linear PLA ionomers. PLA copolymers (CP1-CP3) with pendant alkyne groups were synthesized by reacting L-lactide with propargylated lactide. The existence of copolymers with alkyne groups was unambiguously demonstrated, and the percentage of alkyne was found to be 3-7%. A click reaction protocol was developed to treat the resultant alkyne functionalized copolymers (CP1-CP3) with mercaptosuccinic acid (MSA) and pendant carboxylic acid group functionalized copolymers (CP1-MSA1 to CP3-MSA3) were obtained. The 1-2D NMR confirmed the formation of a major MSA bis-addition product, along with a minor mono-addition product. In the final step, the MSA functionalized copolymers were treated with sodium hydride (NaH) to obtain the corresponding linear PLA ionomers (CP1-MSA1-Na1 to CP3-MSA3-Na3). Significant improvement in thermal and melt rheological properties was observed in these ionomers, as compared to the precursor copolymer and unmodified PLA, due to the microstructural changes caused by the association of the ionic groups. Storage modulus (G `) and loss modulus (G `') values showed a substantial increase in melt elasticity of the ionomers with G ` > G `', whereas the unmodified PLA melt behaved like a viscoelastic liquid. Detailed investigation reveals that incorporating pendant ionic groups in a high molecular weight linear PLA remarkably enhances the elastic modulus from 10 to 100 000 Pa (four orders of magnitude).

Renewable and degradable polyoxalates derived from castor oil - Menon, Abhijith Hari; Joseph, Seena; Shaikh, Maulali H.; Chikkali, Samir H. (Macromolecular Chemistry and Physics, 2025)
Renewable feedstocks pave the way to reduce the demand for petroleum-derived chemicals. Castor oil is one such plant-based raw material that can be used to synthesize chemicals and materials with diverse applications. Herein, we report the synthesis of a novel monomer, 18-methoxy-18-oxooctadec-9-en-7-yl methyl oxalate (3), from castor oil-derived ricinoleic acid. The identity of the monomer 3 has been unambiguously ascertained using 1-2D NMR spectroscopic analysis. Monomer 3 was then subjected to condensation polymerization with potentially bio-renewable long-chain aliphatic diols to yield degradable linear polyoxalates having molecular weights in the range of 8000-22,000 g/mol. The polymerization reactions were performed using pTSA and [Sn(Oct)2] as catalysts, and the polymerization conditions were optimized. The structure of the polymer was confirmed by 1-2D NMR spectroscopy, IR spectroscopy, and GPC analysis. The thermal characterizations of the polyoxalates were carried out by DSC and TGA analysis. The polyoxalates were found to degrade in acidic media. These renewable polyoxalates were further reacted with thiols by ``thiol-ene'' click reaction to produce a cross-linked rubbery polymer, which retained degradability.
Keywords: castor oil derivatives; hydrolytic degradations; polyoxalates